β- and α2-Adrenoceptor Control of Vascular Tension and Catecholamine Release in Female Normotensive and Spontaneously Hypertensive Rats - Berg, Torill (Frontiers in Neurology, 2017)
As in humans, young, female, spontaneously hypertensive rats (SHR) have a lower blood pressure (BP) than male SHR. In male, normotensive rats (WKY), α2- and β1+2-adrenoceptors (AR) reciprocally controlled catecholamine release and vascular smooth muscle tension. This interaction was malfunctioning in male SHR. The present study analysed if a favourable shift in the α2/β1+2AR-interaction may represent an antihypertensive protection in females. Female SHR (early hypertension, 12-14 weeks) and normotensive rats (WKY) were infused with tyramine (15 min) to stimulate norepinephrine release through the re-uptake transporter, consequently preventing re-uptake. Presynaptic control of vesicular release was therefore reflected as differences in overflow to plasma. The released norepinephrine increased total peripheral vascular resistance (TPR). The results showed that β1>2AR facilitated tyramine-stimulated norepinephrine release in both strains, also in the presence of α2AR-antagonist (L-659,066). βAR-antagonist (atenolol-β1, ICI-118551-β2, nadolol-β1+2) had no effect on the increased secretion of epinephrine after L-659,066 in WKY, but β1>2AR-antagonist augmented the L-659,066-induced increase in the secretion of epinephrine in SHR. Nadolol increased the TPR-response to tyramine with a greater effect in WKY than SHR, whereas β1or2-selective antagonists did not. One βAR-subtype may therefore substitute for the other. When both β1+2AR were blocked, α2AR antagonist still reduced the TPR-response in WKY but not SHR. Thus, α2/β1+2AR reciprocally controlled catecholamine release, with a particular negative β1AR-influence on α2AR-autoinhibition of epinephrine secretion in SHR. Moreover, in these female rats, β1/2AR-independent α2AR-mediated vasoconstriction was seen in WKY but not SHR, but β1/2AR-mediated vasodilation down-regulated adrenergic vasoconstriction, not only in WKY but also in SHR.